Outcomes of Conventional External Dacryocystorhinostomy with and without Mitomycin C: Experience from Eastern Nepal - Khadka, Simanta; Joshi, Purushottam; Subedi Basnet, Prava; Pradhan, Chandni (Nepalese Journal of Ophthalmology, 2020)
Introduction: Dacryocystorhinostomy (DCR) is the commonest surgery for nasolacrimal duct obstruction. Inhibition of the scarring process within the anastomosis and rhinostomy site which has been attributed to the failure of this procedure, might improve the success rate of DCR. The objective of this study was to evaluate the outcomes of DCR with Mitomycin-C (MMC) and to compare the results of DCR with and without MMC. Materials and methods: A hospital based, prospective study was conducted in patients with primary acquired nasolacrimal duct obstruction. Standard conventional DCR was performed upto the level of creation of flaps. Application of MMC 0.2 mg/ml in and around the ostium and underneath the created flaps for two minutes was effected with cotton pledgets. The area was thoroughly washed with normal saline after removal of the pledgets. Rest of the surgery was completed as usual. The patients were followed up on the first postoperative day, one month and three months post surgery. Results: A total of 60 cases, 30 in each group were allocated. The success rate of DCR with MMC was found to be 96.7% compared to 86.7% (p=0.35) in the DCR group at the end of three months duration. Conclusions: Intraoperative application of MMC during conventional DCR surgery provides a comparatively higher success rate than DCR without MMC without posing any extra financial burden and adverse drug reaction to the patient.